2019
DOI: 10.1161/strokeaha.119.026848
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Neutrophil Extracellular Traps Reverses Thrombotic Stroke tPA (Tissue-Type Plasminogen Activator) Resistance

Abstract: Background and Purpose— Recanalization of the occluded artery is a primary goal in stroke treatment. Unfortunately, endovascular treatment is not always available, and tPA (tissue-type plasminogen activator) therapy is limited by its narrow therapeutic window; importantly, the rate of early arterial recanalization after tPA administration is low, especially for platelet-rich thrombi. The mechanisms for this tPA resistance are not well known. Since neutrophil extracellular traps (NETs) have been imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 32 publications
6
97
0
3
Order By: Relevance
“…Of interest, we recently reported that elevated NET formation was associated with microvascular occlusion and cerebral hypoperfusion after acute brain injury in both mice and humans [143]. Conversely, administration of recombinant human DNase-I, an FDA-approved drug under investigation for the management of COVID-19-induced ARDS [144], improved blood flow and outcomes after both experimental stroke and traumatic brain injury [143,[145][146][147]. Thus, the widespread generation of NETs after SARS-CoV-2 may provide a potential target to reduce acute and chronic neurological consequences, including headache, elevated stroke risk, and potential cognitive issues due to COVID-19.…”
Section: Do Coagulopathies Contribute To the Neurological Consequencementioning
confidence: 99%
“…Of interest, we recently reported that elevated NET formation was associated with microvascular occlusion and cerebral hypoperfusion after acute brain injury in both mice and humans [143]. Conversely, administration of recombinant human DNase-I, an FDA-approved drug under investigation for the management of COVID-19-induced ARDS [144], improved blood flow and outcomes after both experimental stroke and traumatic brain injury [143,[145][146][147]. Thus, the widespread generation of NETs after SARS-CoV-2 may provide a potential target to reduce acute and chronic neurological consequences, including headache, elevated stroke risk, and potential cognitive issues due to COVID-19.…”
Section: Do Coagulopathies Contribute To the Neurological Consequencementioning
confidence: 99%
“…Granulocyte recruitment during ischemia/reperfusion in the heart of WT mice was shown, which was later associated with the modulation of chemokines that drive infiltration and adhesion [ 92 ]. In addition, neutrophil extracellular traps (NETs) have recently been linked to different CV diseases, such as arteriosclerosis [ 93 ], ischemic stroke [ 94 ], thrombotic stroke [ 95 ], acute coronary syndrome [ 96 ], and others. However, there is no direct evidence of the participation of NETs in AH.…”
Section: Discussionmentioning
confidence: 99%
“…NETs can be dismantled by DNAse I treatment or by heparin (121), while their production has been blocked with PAD-4 inhibitors, mostly chloramidine (Cl-Amidine). Disruption of NETs with DNAse I have proven efficient in mouse models of stroke (122), ischemia reperfusion (123, 124), heparin-induced thrombocytopenia (125), and deep vein thrombosis (126). Furthermore, mice treated with DNAse I show less metastasis in mammary tumor models (127, 128).…”
Section: Diagnostic and Therapeutic Perspectivesmentioning
confidence: 99%
“…Furthermore, mice treated with DNAse I show less metastasis in mammary tumor models (127, 128). Treatment with chloramidine has shown efficacy in murine models of abdominal aortic aneurysm (122), arterial thrombosis (129), photothrombotic stroke (122), and sepsis (130).…”
Section: Diagnostic and Therapeutic Perspectivesmentioning
confidence: 99%